Obesity-Associated Alterations of Natural Killer Cells and Immunosurveillance of Cancer - Bähr, Ina; Spielmann, Julia; Quandt, Dagmar; Kielstein, Heike (Frontiers in Immunology, 2020)
Obesity is accompanied by a systemic chronic low-grade inflammation as well as dysfunctions of several innate and adaptive immune cells. Recent findings emphasize an impaired functionality and phenotype of natural killer (NK) cells under obese conditions. This review provides a detailed overview on research related to overweight and obesity with a particular focus on NK cells. We discuss obesity-associated alterations in subsets, distribution, phenotype, cytotoxicity, cytokine secretion, and signaling cascades of NK cells investigated in vitro as well as in animal and human studies. In addition, we provide recent insights into the effects of physical activity and obesity-associated nutritional factors as well as the reduction of body weight and fat mass on NK cell functions of obese individuals. Finally, we highlight the impact of impaired NK cell physiology on obesity-associated diseases, focusing on the elevated susceptibility for viral infections and increased risk for cancer development and impaired treatment response.